Effects of tuber size, soaking hours and sprouting media on sprouting of tiger nut (Cyperus esculentus L. var. sativa) tubers - Thomas Oladeji Fabunmi; Sunday Ojo Adigbo; Joy Nwakaego Odedina; Yanmife Iyanu Akinsanya (Acta Agriculturae Slovenica, 2016)
Tiger nut, Cyperus esculentus L., is one of the underutilized and neglected food crops in most parts of the world leading to limited information on its production technology. A trial arranged in a 3×4×2 factorial of a completely randomized design was conducted in a green house of the Federal University of Agriculture, Abeokuta, Nigeria, to evaluate the effects of tuber size (large, medium and small), soaking duration (0, 24, 48 and 72 hours) and sprouting media (cotton wool and polythene bag) on the sprouting of tiger nut. Significant interactions were observed between growth media and soaking hours as well as between tuber sizes and soaking hours on the sprouting of tiger nut. Soaking beyond 24 hours before placement in sprouting medium led to a significant reduction in number of sprouted tubers in polythene bags. Small sized tubers had reduced (p<0.05) number of sprouts when soaked beyond 24 hours. Sprouting of tiger nut was better using medium size tubers soaked for 24 hours and placed between layers of cotton wool.